Towards a maqasid-based theory of human needs - Jaffer, Usman; El-Mesawi, Mohamed El-Tahir (IIUM Press, International Islamic University Malaysia, 2017)
This work explores and outlines a possible needs theory that is compatible with the Islamic world view. The need for such a theory arises from the fact that needs theories which are in existence originate in secular Western ideologies, especially in the realm of psychology. Western psychological theories omit the existence of God and the soul from their conceptualisations and thus formulate incomplete views of human nature. This has led to inadequate needs theories. The present work is a qualitative, textual, theoretical and analytical study. In terms of human nature, the schools of Evolution, Psychodynamics, Behaviourism, Social and Humanistic Psychology are explored